2014
DOI: 10.1016/j.dcn.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

But do you think I’m cool?

Abstract: The current fMRI study investigated the neural foundations of evaluating oneself and others during early adolescence and young adulthood. Eighteen early adolescents (ages 11–14, M = 12.6) and 19 young adults (ages 22–31, M = 25.6) evaluated if academic, physical, and social traits described themselves directly (direct self-evaluations), described their best friend directly (direct other-evaluations), described themselves from their best friend’s perspective (reflected self-evaluations), or in general could cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 100 publications
3
52
0
Order By: Relevance
“…The subgenual ACC is thought to integrate emotional and cognitive signals into decision making processes, integrate conflictive information (Phillips et al, 2003b, c; Phillips et al, 2008), and to support implicit emotion regulation given its interconnections with limbic structures (Bush et al, 2000; Davis et al, 2005). Indeed, rMPFC activation has previously been identified during self-processing in typically-developing adolescents (Dégeilh et al, 2015; Jankowski et al, 2014). Thus, our findings replicate and extend prior research regarding psychologically healthy youth.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The subgenual ACC is thought to integrate emotional and cognitive signals into decision making processes, integrate conflictive information (Phillips et al, 2003b, c; Phillips et al, 2008), and to support implicit emotion regulation given its interconnections with limbic structures (Bush et al, 2000; Davis et al, 2005). Indeed, rMPFC activation has previously been identified during self-processing in typically-developing adolescents (Dégeilh et al, 2015; Jankowski et al, 2014). Thus, our findings replicate and extend prior research regarding psychologically healthy youth.…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, processing information regarding the self reliably engages both anterior and posterior cortical midline structures (CMS), including rostral and perigenual anterior cingulate cortex (ACC), posterior cingulate cortex (PCC), precuneus and medial PFC, particularly medial BA10 (Ichikawa et al, 2011; Kircher et al, 2000). Additionally, dorsal ACC recruitment has been noted during social rejection or negative evaluation (Rotge et al, 2015), and when healthy adolescents engage in both direct (self perspective) and indirect (important others’ perspectives) self-referential processing (Jankowski et al, 2014; Pfeifer et al, 2009). Although limited in scope, existing research has shown that self-injuring youth and adults demonstrate hyperactivation of CMS regions (i.e., ACC, PCC) during emotionally distressing tasks (Davis et al, 2014; Plener et al, 2012), perhaps suggesting self-injurers’ atypical processing of self-related information during heightened emotional demand.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the comparison of adults and adolescents, we did not have a sufficiently large number of participants to isolate influences of these and other potentially important variables on the anxiety-brain function relationship. Mounting evidence suggests sex (Guyer, Caouette, Lee, & Ruiz, 2014; Guyer, Choate, Pine, & Nelson, 2012; Guyer et al, 2009; Lee et al, 2014) and pubertal stage (Jankowski, Moore, Merchant, Kahn, & Pfeifer, 2014; Klapwijk et al, 2013) based differences in brain and behavioral responses to social stimuli. We had insufficient power to test for interactions among sex, pubertal development, social anxiety, and age group.…”
Section: Discussionmentioning
confidence: 99%
“…Most of this work has examined self-evaluation, typically by asking youth to judge whether various (often overtly positive or negative) traits and attributes describe them. Like adults, children and early adolescents use cortical and subcortical midline structures, in particular, the ventromedial prefrontal cortex (vmPFC) and adjacent rostral/perigenual anterior cingulate cortex (ACC), more when evaluating themselves than when evaluating others (10-12; although this pattern can be attenuated with close others like adolescents' best friends 13,14). Even in clinical populations of children and adolescents, the vmPFC is usually more active during self-evaluations than in most control conditions.…”
Section: The Development Of Self and Identity In Adolescencementioning
confidence: 99%